Persistence of envelopes in different CD4+ T-cell subsets in antiretroviral therapy-suppressed people with HIV. (1st February 2023) - Gartner, Matthew J.; Tumpach, Carolin; Dantanarayana, Ashanti; Stern, Jared; Zerbato, Jennifer M.; Chang, J. Judy; Angelovich, Thomas A.; Anderson, Jenny L.; Symons, Jori; Deeks, Steve G.; Flynn, Jacqueline K.; Lewin, Sharon R.; et al.
Abstract : Objectives: Despite suppressive antiretroviral therapy (ART), HIV can persist in a diverse range of CD4 + T-cell subsets. Through longitudinal env sampling from people with HIV (PWH) on ART, we characterized the persistence and phenotypic properties of HIV envs over two time-points (T1 and T2). Methods: Longitudinal blood and lymphoid tissue samples were obtained from eight PWH on suppressive ART. Single genome amplification (SGA) was performed on env to understand the genetic diversity and degree of clonal expansions over time. A subset of envs were used to generate pseudovirus particles to assess sensitivity to autologous plasma IgG and broadly neutralizing antibodies (bNAbs). Results: Identical env sequences indicating clonal expansion persisted between T1 and T2 and within multiple T-cell subsets. At both time-points, CXCR4-tropic (X4) Envs were more prevalent in naive and central memory cells; the proportion of X4 Envs did not significantly change in each subset between T1 and T2. Autologous purified plasma IgG showed variable neutralization of Envs, with no significant difference in neutralization between R5 and X4 Envs. X4 Envs were more sensitive to neutralization with clinical bNAbs, with CD4-binding site bNAbs demonstrating high breadth and potency against Envs. Conclusion: Our data suggest the viral reservoir in PWH on ART was predominantly maintained over time through proliferation and potentially differentiation of infected cells. We found the humoral immune response to Envs within the latent reservoir was variable between PWH. Finally, we identified coreceptor usage can influence bNAb sensitivity and may need to be considered for future bNAb immunotherapy approaches.